2020
DOI: 10.1074/mcp.ra120.002079
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Exosome Cargo by Mutant Tau Expressed in Human-induced Pluripotent Stem Cell (iPSC) Neurons Revealed by Proteomics Analyses

Abstract: Accumulation and propagation of hyperphosphorylated Tau (p-Tau) is a common neuropathological hallmark associated with neurodegeneration of Alzheimer's disease (AD), frontotemporal dementia and parkinsonism linked to chromosome 17 (FTDP-17), and related tauopathies. Extracellular vesicles, specifically exosomes, have recently been demonstrated to participate in mediating Tau propagation in brain. Exosomes produced by human induced pluripotent stem cell (iPSC)-derived neurons expressing mutant Tau (mTau), conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 145 publications
(158 reference statements)
2
39
0
Order By: Relevance
“…On its own right, IFITM3 induction is not restricted to intracellular cascades. IFITM3 has been previously shown to be a mutant-tau exclusive cargo in AD exosomes 33 , whereas IFITM3-loaded exosome trafficking from infected to non-infected cells has been shown to confer resistance to DENV infection 34 . On these premises, IFITM3, exosomal hyperphosphorylated tau 35 and Αβ-ΝΑ may constitute a feed-forward signal expanding from a primary site of neuroinfection (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…On its own right, IFITM3 induction is not restricted to intracellular cascades. IFITM3 has been previously shown to be a mutant-tau exclusive cargo in AD exosomes 33 , whereas IFITM3-loaded exosome trafficking from infected to non-infected cells has been shown to confer resistance to DENV infection 34 . On these premises, IFITM3, exosomal hyperphosphorylated tau 35 and Αβ-ΝΑ may constitute a feed-forward signal expanding from a primary site of neuroinfection (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that exosomes are sufficient to cause the long-distance propagation of tau pathology and neurodegeneration in vivo. To further understand the dysregulation of pathogenic exosomes, they were analyzed using proteomics and bioinformatics in the study of Podvin et al [ 62 ]. They found that the expression of the P301L and V337M mutations of tau in human iPSC neurons results in the recruitment of distinct proteins to exosomes.…”
Section: Application Of Hipscs-derived Exosomes In Diseasesmentioning
confidence: 99%
“…Table 2 summarizes some of the exosome proteins used as biomarkers in studies of neurodegeneration. A recent quantitative proteomics study exploring the differential expression of proteins in exosomes derived from iPSC neurons transfected with mutant Tau (P301L and V337M) (mTau) showed significant alteration in protein expression compared to control exosomes [ 89 ]. Proteomic analyses identified 347 and 574 proteins in mTau and control exosomes, respectively.…”
Section: Proteomics Approaches In Exosomal Protein Biomarker Discomentioning
confidence: 99%
“…Eighteen proteins were unique to mTau exosomes, wheras 245 proteins were found only in control exosomes. Proteins unique to mTau exosomes included acidic nuclear phosphoprotein 32 family member A (ANP32A), AP-2 complex subunit α-1 (AP2A1), and V-type proton ATPase catalytic subunit A, that have been shown to be involved in synaptic dysfunction, memory loss and neuropathology [ 89 ]. Studies of exosome-mediated secretion of phosphorylated Tau from human neuroblastoma cells have shed light onto the possible role of exosomes in Tau pathophysiology in AD [ 90 ].…”
Section: Proteomics Approaches In Exosomal Protein Biomarker Discomentioning
confidence: 99%